Nanossistemas poliméricos para tratamento do câncer de pulmão: o efeito corona proteica - Saladine, Maria Eduarda da Silva (Universidade Federal de São Carlos, 2025)
Lung cancer is the leading cause of cancer mortality, with cisplatin being widely used in its treatment despite its low tumor specificity and high systemic toxicity. PLGA polymeric nanoparticles emerge as an alternative to improve drug delivery; however, in biological media, they interact with proteins, forming the protein corona, which can alter their properties and biological effects. This study evaluated the influence of surface charge and incubation time on protein corona formation, as well as its cytotoxic effects on A549 cells. PLGA nanoparticles, with and without chitosan coating, were incubated in a medium containing fetal bovine serum and characterized regarding size, zeta potential, protein concentration, morphology, and chemical structure. The nanoparticles exhibited spherical morphology, an average size of 75 nm, a zeta potential of –18 mV, and an encapsulation efficiency of 28%. The formation of the protein corona was evidenced by a size increase of approximately 30 nm and a change in surface charge, with higher protein adsorption observed in positively charged nanoparticles and greater protein interaction after 1 h of incubation. The presence of the protein corona resulted in higher cell viability compared to corona-free nanoparticles and free cisplatin, although additional release and internalization studies are required to clarify the lower cytotoxicity observed. The results highlight the importance of the protein corona in modulating the biological interactions of PLGA nanoparticles and in developing safer and more effective nanostructured systems for lung cancer treatment
Polymeric nanosystems for lung cancer treatment: the protein corona effect
Keywords: Câncer de pulmão; nanopartículas; corona proteica; CIENCIAS DA SAUDE; 3. Saúde e Bem-Estar